2006
DOI: 10.1021/nl052458a
|View full text |Cite
|
Sign up to set email alerts
|

NSET Molecular Beacon Analysis of Hammerhead RNA Substrate Binding and Catalysis

Abstract: Nanometal surface energy transfer (NSET), which describes an energy transfer event from optically excited organic fluorophores to small metal nanoparticles, may be used as a molecular beacon/ruler similar to FRET, but with advantages over this classical technique. Here we use NSET to measure Mg(2+)-induced conformational changes for a hammerhead ribozyme and confirm these measurements using FRET. These optical experiments enhance our understanding of the different kinetic pathways for this ribozyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(167 citation statements)
references
References 33 publications
7
159
0
1
Order By: Relevance
“…NSET has mainly been found to be in good agreement with experimental data (using organic dyes and quantum dots as donors) if the nanoparticles are of small size (below about 3 nm diameter) and thus do not have any plasmon bands [79,80,82,84,87,88]. Nevertheless, also larger Au nanoparticles of up to 18 nm diameters showed experimental NSET behavior [77,78,90,91].…”
Section: Bret and Cretsupporting
confidence: 74%
See 2 more Smart Citations
“…NSET has mainly been found to be in good agreement with experimental data (using organic dyes and quantum dots as donors) if the nanoparticles are of small size (below about 3 nm diameter) and thus do not have any plasmon bands [79,80,82,84,87,88]. Nevertheless, also larger Au nanoparticles of up to 18 nm diameters showed experimental NSET behavior [77,78,90,91].…”
Section: Bret and Cretsupporting
confidence: 74%
“…Copyright 2012, American Chemical Society.) distance dependence, which has been investigated in theory [71][72][73][74][75][76] and in practice for different energy donors such as organic dyes [77][78][79][80][81][82][83][84], semiconductor quantum dots [85][86][87][88][89][90], or fluorescent proteins [91]. Among all these different systems, different mechanisms have been proposed to be responsible for the energy transfer and a general model for energy transfer to metal nanoparticles does not exist.…”
Section: Bret and Cretmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular beacon-based assays for DNA sensing measurements, for example, produce 100-fold sensitivity enhancements using Au NMs compared to previous dye-dye combinations [466][467][468][469]. Au NP-fluorophore complexes show promise for in vitro diagnostic applications as "noses," with the ability to discern between various bacteria species and strains, proteins in complex solutions, and between cancerous and healthy cell lines [470].…”
Section: 53mentioning
confidence: 99%
“…As such, the use of AuNPs as energy acceptors enables the energy transfer to be valid even in the excess distance of the traditional FRET. One of the feasible mechanisms might be associated with the property of metal surface; it was reported that the metal surface extended the effective energy transfer distance up to 22 nm, resulting in a high energy transfer efficiency (Dulkeith et al, 2002;Jennings et al, 2006a;Jennings et al, 2006b;Pons et al, 2007;Yun et al, 2005). The initial report of protease detection with a QD-AuNP system was made by Chang et al (Chang et al, 2005).…”
Section: Qdmentioning
confidence: 99%